INDUSTRIAL WASTE REUSE: PROSPECTS FOR PRODUCING COMPLEX FERTILIZERS FROM LOCAL PHOSPHATE WASTE (Universal International Scientific Journal, 2026)
The study analyzed the theoretical and practical foundations of the technology for producing complex mineral fertilizers from local phosphate waste. The chemical composition of phosphorite powder and phosphate sludge was studied, and methods for their processing into liquid and suspension fertilizers by acidic decomposition were developed. The results of the study showed that waste processing not only reduces the environmental load, but also increases the efficiency of using raw materials by 30–40%. The proposed technology is consistent with the principles of the "Green Economy" and serves to form a resource-saving and waste-free production system in the chemical industry of Uzbekistan
Keywords: phosphate waste; liquid fertilizers; suspension fertilizers